Pendidikan Kesehatan Lingkungan Melalui Kultum - Iswahyudi Haryono, Yayi Suryo Prabandari, Widodo Hariyono (Fakultas Kedokteran Universitas Gadjah Mada, 2008)
Background: The condition of environmental health in Indonesia is still not good. This is noticed with high morbidity rate of Acute Respiratory Infection (ARI), diarrhea, skin and TBC diseases. This condition is occurred in pondok pesantren (moslem school) which is spread out in the District of Bener Meriah Province of Nanggroe Aceh Darussalam (NAD). Therefore, health promotion effort which considered value, norm as well as local resources is necessary. Kultum (kuliah tujuh menit/seven minutes speech) is one of media which could be used to convey da’wah (moslem learning) so that kultum can be used as media to conveys enviromental health message.Objective: The general objective of this research was aimed to find out the improvement knowledge, attitude and behavior related to the health environment through kultum method by ustadz toward pesantren community.Method: This was a quasi experiment research and the population was santri (moslem student in moslem school) and the subject for each group was all santri. The independent variable was health education through kultum and dependent variable were knowledge, attitude and behavior of santri regarding environmental health. The research instrument being used was questionnaire and observation check list. Data analysis was conducted by using independent sample t test and paired sample t test.Result: The result of statistic analysis showed that knowledge, attitude and behavior regarding environmental health of santri who were given health education through kultum with hand out were different with those who were not given kultum intervention. This was showed by the increasing average value score of knowledge, attitude and behavior of santri who were given environmental health education through kultum in post test 1 and 2. The routinity of environmental health message which is obtained by santri through kultum, conveying environmental health message which was implemented in religious situation as well as figure of guru/ustadz that was credible and respected in pesantren effected on the changes of knowledge, attitude and behavior of santri toward positive respond.Conclusion: Knowledge, attitude and behavioral of santri who were given environmental health education through kultum better than santri who were not given intervention kultum. Kultum as da’wah media could be used to conveys health message in pesantren, mosque or praying forum.Keywords: knowledge, attitude and behavior of santri